Enhanced Catalytic Electrochemical Reduction of Dissolved Oxygen with Ultraclean Cucurbituril[7]-Capped Gold Nanoparticles - Pino-Lopez, E (Royal Society of Chemistry, 2014)
Gold nanoparticles capped with cucurbituril[7] have been prepared in the absence of metallic cations and organic ligands. Remarkably, these nanohybrids encapsulate dissolved oxygen and are highly active in electrochemical reduction. The effect of the presence of sodium and ammonium salts on this catalysed process is also analysed. © 2014 the Partner Organisations.